2017
DOI: 10.3389/fpls.2017.00354
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Introgression of the Fusarium Wilt Resistance Gene into an Elite Cabbage Line through the Combined Application of a Microspore Culture, Genome Background Analysis, and Disease Resistance-Specific Marker Assisted Foreground Selection

Abstract: Cabbage is an economically important vegetable worldwide. Cabbage Fusarium Wilt (CFW) is a destructive disease that results in considerable yield and quality losses in cole crops. The use of CFW-resistant varieties is the most effective strategy to mitigate the effects of CFW. 01-20 is an elite cabbage line with desirable traits and a high combining ability, but it is highly susceptible to CFW. To rapidly transfer a CFW resistance gene into 01-20 plants, we used microspore cultures to develop 230 doubled haplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Our group developed several elite Ogura-CMS cabbage lines with excellent agronomic performance [ 5 ], and they have been successfully used for the hybrid seed production of many elite varieties. F01-20 is an elite cabbage line originally introduced from Canada [ 28 ], and its Ogura-CMS line CMS01-20 was bred through crosses with a different Ogura-CMS line using F01-20 as the male parent and subsequent recurrent backcrossing with F01-20 for more than 20 generations. The very similar genetic backgrounds of this CMS line and its maintainer line make them ideal materials for cabbage breeding as well as for studying the molecular mechanisms of Ogura-CMS.…”
Section: Introductionmentioning
confidence: 99%
“…Our group developed several elite Ogura-CMS cabbage lines with excellent agronomic performance [ 5 ], and they have been successfully used for the hybrid seed production of many elite varieties. F01-20 is an elite cabbage line originally introduced from Canada [ 28 ], and its Ogura-CMS line CMS01-20 was bred through crosses with a different Ogura-CMS line using F01-20 as the male parent and subsequent recurrent backcrossing with F01-20 for more than 20 generations. The very similar genetic backgrounds of this CMS line and its maintainer line make them ideal materials for cabbage breeding as well as for studying the molecular mechanisms of Ogura-CMS.…”
Section: Introductionmentioning
confidence: 99%
“…Cabbage is an important vegetable crop due to its wide adaptability, strong resistance, healthcarerelated value, and favorable taste [44]. Recently, increasing studies of important traits in cabbage have been reported, including petal color, yellow-green leaf, glossy green, hybrid lethality, Fusarium wilt and self-incompatibility [45][46][47][48]. These studies not only enrich the germplasm resources of cabbage but also promote the exploration of the molecular mechanism of cabbage.…”
Section: Discussionmentioning
confidence: 99%
“…Introgression populations consist of a set of introgression lines or families, constructed by continuous backcrossing to the recurrent parent, while carrying a limited number of chromosome segments from a donor parent in their genomes. In crop breeding, introgression populations were used to improve some traits of a crop variety, especially when a variety was found to be sensitive to a specific disease, drought stress or lodging (Dutra et al., ; Liu, Han, et al., ; Liu, Li, et al., ). Introgression populations were also used for pyramiding multiple quantitative trait locus/loci (QTL) in the same background (Liu et al., ; Reinke, Kim, & Kim, ), generating varieties with multiple beneficial alleles.…”
Section: Introductionmentioning
confidence: 99%